THE IMPACT OF STOCK RETURNS, INVESTMENT RISK, AND FINANCIAL LITERACY ON THE INVESTMENT INTEREST OF MILLENNIALS - Maria Yovita R. Pandin; Abigaiel Lesbasa; Kemberly S. Kambuaya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The Indonesian capital market has seen a rise in retail investor participation from millennials, suggesting a shift towards a more mature financial orientation. Research indicates that while stock returns are a key driver of interest, millennials are reactive to short-term changes and susceptible to misinformation. The relationship between investment risk and interest is complex, as millennials display both risk-averse and risk-taking behaviors based on emotional influences. Financial literacy is crucial for informed decision-making, yet disparities in access to education, particularly in regions like Maluku and Papua, hinder its effectiveness. Method: This study uses a causal analysis design with quantitative research methods. The data in this study was obtained directly from questionnaires given to respondents. The population in this study consisted of students and workers from Maluku and Papua aged 17-31 years. Simultaneously, the three variables, namely Stock Return (X1), Investment Risk (X2), and Financial Literacy (X3), have a significant effect on the Investment Interest (Y) of the millennial generation. This shows that economic factors and individual ability to understand finance together influence the investment decisions of the younger generation. Result: The results of this study are in line with investment theory and previous studies which state that return, risk, and financial literacy are the main factors that influence individual investment behavior. Stock returns have a positive and significant effect, investment risk has a negative and significant impact, and financial literacy has a positive and significant effect on the investment interest of millennials. Keywords: Financial Literacy, Investment Interest, Investment Risk, Millennials, Stock Returns